Experience of Acceptance and Commitment Therapy for those with mild traumatic brain injury (ACTion mTBI): A qualitative descriptive study - Josh W. Faulkner; Jason Chua; Amabelle Voice-Powell; Deborah L. Snell; Maree Roche; John Moffat; Suzanne Barker-Collo; Alice Theadom (PLoS ONE, 2025)
Psychological interventions may make a valuable contribution to recovery following a mild traumatic brain injury (mTBI) and have been advocated for in treatment consensus guidelines. Acceptance and Commitment Therapy (ACT) is a more recently developed therapeutic option that may offer an effective approach. Consequently, we developed ACTion mTBI, a 5-session ACT-informed intervention protocol. To establish the feasibility of this intervention, we wanted to understand participants’ experiences of ACTion mTBI, determine acceptability and identify any refinements needed to inform a full-scale effectiveness trial. We recruited adults (≥16 years of age) diagnosed with mTBI who were engaged in community-based multidisciplinary rehabilitation. After completing the ACTion mTBI sessions, 23/27 (85.2%) participants (mean time post-injury: 28.0 weeks) completed a semi-structured interview about their experience of the intervention. Interviews were audio-recorded, transcribed verbatim and analysed using a qualitative description approach. There were two overarching themes 1) attacking the concussion from a different direction and 2) positive impact on recovery which depicted participants’ overall experiences of the intervention. Within these overarching themes, our analysis also identified two subthemes: 1) helpful aspects of the intervention which included education and ACT processes (i.e., being present and being able to step back) and 2) “contextual factors that enabled intervention effectiveness” which included being equipped with tools, cultural and spiritual responsiveness, the therapeutic connection, and the intervention having a structured yet flexible approach to order of delivery to meet individual needs. Participants’ experiences support acceptability, cultural and spiritual responsibility of ACTion mTBI. Suggested refinements included enabling access to intervention over time, not just at one point during recovery and the addition of a brief check-in follow-up.